Increasing Fruit and Vegetable Consumption and Offerings to Somali Children - Mary O. Hearst; Rebecca Kehm; Shelley Sherman; Kate E. Lechner (SAGE Publishing, 2014)
Objective : To determine the feasibility, acceptability, and impact of a parent-centered intervention to increase fruit and vegetable servings and consumption among Somali children living in the United States. Design : Pilot intervention that included Somali community health workers who organized groups of 3 or 4 women to participate in 2 initial educational sessions, including topics of health and nutrition, serving size, and label reading. A third session taught interactive cooking to increase skills in preparing fruits and vegetables and increasing the numbers of vegetables included in traditional Somali dishes. The final session was a trip to the grocery store to identify fruits and vegetables, determine ripeness, and explore frozen and canned fruits and vegetables for halal, low-sodium, and low-sugar products. Surveys were completed pre- and post-intervention. Setting : Study participants were recruited from a large housing complex in Minneapolis, Minnesota, with a high population of Somali immigrants. Participants : Somali women (N = 25) with children aged 3 to 10 years. Results : The intervention was feasible and well accepted. In comparing pre- and post-intervention surveys, mothers reported providing their children significantly more frequent servings of fruits and vegetables at dinner, lunch, snack, and breakfast (vegetable only). There was a statistically significant increase in parent-reported intake of fruits and vegetables for themselves and their children. Conclusion : The FAV-S study was feasible and acceptable, and it demonstrated potential for increasing fruit and vegetable servings and consumption among Somali children. A larger-scale randomized trial is needed to assess the impact of this intervention.